Strategi Penerapan Kurikulum Berbasis Outcome Based Education di Sekolah Tinggi Pastoral Dian Mandala Gunungsitoli - Sergius Lay (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Outcome-Based Education (OBE) has emerged as a strategic approach to improving graduate quality in higher education, including pastoral colleges. The pastoral education context in Indonesia, particularly in island regions such as Nias, requires the integration of academic, spiritual, and pastoral dimensions in the learning process. This study aims to analyze the strategies for implementing OBE at the Pastoral College Dian Mandala Gunungsitoli and to identify its supporting factors and challenges. A qualitative research design with a literature review approach was applied, drawing on 25 scientific articles published between 2021 and 2025. The analysis involved identifying main themes, categorizing supporting and challenging factors, and synthesizing strategies for implementation. The findings indicate that OBE implementation includes developing curriculum documents aligned with the Indonesian National Qualification Framework (KKNI) and National Standards of Higher Education (SN-Dikti), strengthening faculty capacity through training, integrating innovative learning models, and applying authentic assessment that evaluates both academic and spiritual competencies. Supporting factors consist of institutional leadership commitment, the availability of curriculum information systems, and collaboration with external stakeholders. Major challenges involve limited faculty understanding of OBE, inadequate technological infrastructure, and resistance to changes in academic culture. This study concludes that OBE can enhance graduates’ competencies and strengthen pastoral identity, provided that faculty training, internal quality assurance systems, and the integration of local wisdom into the curriculum are consistently developed.